Influence of feed substitution with acorns on fattening performance, carcass characteristics, and meat composition of Prestice Black-Pied pigs finished in a conventional indoor system - Jaroslava Belkova; Miroslav Rozkot; Eva Weisbauerova; Jana Truneckova (Cogent Food & Agriculture, 2023)
AbstractWith their considerable nutritive value, acorns have long been a natural feed source for pigs and, in recent years, fattening pigs with acorns has become very popular even in countries where it has not traditionally been customary. The meat of pigs finished with acorns has a unique flavour and fat profile as reflected by fatty acids content. We decided to determine the nutritional value of the most common species of acorns in Central Europe (Quercus robur) and examine the effects of this feed upon fattening performance, carcass value, and the composition of meat and fat produced by indoor finishing of pigs, as forest grazing is prohibited here. We conclude that the Prestice Black-Pied breed can be fattened utilizing a mixed feed containing acorns at the level of 10% under intensive conditions without significantly changing the performance parameters (average daily gain was 750 g versus 761 g in the control group). We found improvements in fatty acid profiles of intramuscular fat away from saturated toward monounsaturated. The improvements in the fatty acid profiles, similar to those seen in pigs raised in sylvan settings, create pork that may benefit human health. Acorns can constitute an alternative feedstuff even for pigs finished indoors and bring new benefits to agriculture in modern times.